ESTABLISHING THE RELATIONSHIP BETWEEN VARIOUS METASTATIC LUNG LESIONS WITH GENDER AND AGE - Nortozhiev Jahongir Muhammad ugli; Turabov Navruz Norjigit ugli; Rakhimova Durdona Zhurakulovna (Web of Journals Publishing, 2024)
This article discusses the prevalence of metastatic lung lesions among women and men of different ages and the factors that may contribute to the detection of such results.